تجديد الدرس العقدي وسؤال المقاصد - درار، نسمة; رجاتى، نورة Rajati, Nourah (جامعة الشهيد حمّه لخضر الوادي - معهد العلوم الإسلامية, 2023)
عم الاهتمام بمقاصد الشريعة في مصنفات القدماء والمحدثين، وحصرت العناية بها، حتى استهجن بعض الباحثين بحث مقاصد العقائد، متعللا بعدم جواز تعليل أفعال الله، بينما رأى فريق أخر أن للعقيدة الإسلامية مقاصد سامية تحرر الولاء لله رب العالمين، فواجه الدرس العقدي مشكلة من حيث تغييب النظر المقاصدي في المعاني والحِكم والأسرار الإلهية التي انطوت عليها قضايا الإيمان والعقيدة، ذلك بأن النظر المبني على التقعيد والنقد والتحليل والتأطير غيَّر النظر التقليدي، ولأن مصلحة الأمة تقتضي تجديد الدرس العقدي ومناهجه. ولكي يحقق الدرس العقدي أبعاده الوظيفية في محاربة الانحرافات السلوكية في واقع المسلمين، فإنه مطالب بالتجديد، وبعث الروح فيه كي يساعد على العمل، ويمكن له في النفوس، وذلك بإعماله للنظر المقاصدي، بعيدا عن الدرس المكتفي بمجرد الوعظ والإلقاء والتلقين بالاعتماد على كتب الحواشي والشروح القديمة، وتأتي هذه الدراسة إيمانا بحاجة الدرس العقدي الملحة للنظر المقاصدي وتأكيدا لأهمية مقاصد العقائد ودورها في الإسهام في تطوير الدرس العقدي من خلال إبراز أهمية دور مقاصد العقيدة وضرورة تفعيلها. Attention to the intents of Sharia prevailed in the works of the ancients and moderns, and attention was limited to them, to the extent that some researchers deplored the research of the intents of doctrines, pretending the inadmissibility of justifying God’s actions, while another group saw that the Islamic doctrine has lofty intents that liberate loyalty to God, Lord of the worlds, so the dogmatic lesson faced a problem in terms of neglecting intentional consideration of the meanings, wisdom, and divine secrets involved in the issues of faith and doctrine, because the consideration based on criticism, analysis and framing is not the traditional view, and because the nation’s interest requires the renewal of the doctrinal lesson and its methods, and within the context of achieving the functional dimensions of faith and combating behavioral deviations in the reality of Muslims, it is required to renew and to try to resurrect the spirit in it in order to help work and be empowered in the souls, by implementing the intentional consideration, away from the study which is limited to mere preaching, uttering and indoctrination by relying on the books of footnotes and ancient explanations. This study comes as a belief in the vital necessity of the doctrine lesson to the intentional consideration confirming the importance and the role o f the doctrinal intents in contributing to the development of the doctrinal lesson through highlighting the importance of the role of the intents of the doctrine and the necessity of trying to activate them.
Keywords: الشريعة الإسلامية -- الانحرافات السلوكية -- العقيدة الإسلامية